Inland shipping and navigation delegate information : Thursday 16 October 1997, One Great George Street Conference Centre, the Institution of Civil Engineers, London. (Thomas Telford series of the Institution of Civil Engineers' seminars., 1997)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 16 October 1997.